Comparison of pulmonary lesions using lung ultrasound and high-resolution computed tomography in adult patients with primary humoral immunodeficiencies - Ziętkiewicz, Marcin; Buda, Natalia; Więsik-Szewczyk, Ewa; Piskunowicz, Maciej; Grzegowska, Dominika; Jahnz-Różyk, Karina; Zdrojewski, Zbigniew (Frontiers in Immunology, 2022)
Pulmonary involvement is the most common complication in patients with predominantly antibody deficiencies (PADs). Therefore, patients require repeated imaging tests. Unlike high-resolution computed tomography (HRCT), lung ultrasonography (LUS) does not expose patients to X-rays or contrast agents, and can be performed even at the bedside. This study aimed to evaluate lung lesions using simultaneous LUS and HRCT in a group of patients with PADs. Twenty-nine adult patients (13 women and 16 men) diagnosed with PADs according to the ESID criteria (23 Common variable immunodeficiency, 2 X-linked agammaglobulinemia, 2 IgG subclass deficiencies, and 2 Unspecified hypogammaglobulinemia) were included in the study. The mean age was 39.0 ± 11.9 years. The mean time elapsed between the first symptoms of PADs and the examination was 15.4 ± 10.1 years. Lung ultrasonography and high-resolution computed tomography were performed simultaneously according to a defined protocol during the clinic visits. In both examinations, lesions were compared in the same 12 regions: for each lung in the upper, middle, and lower parts, separately, front and back. A total of 435 lesions were described on LUS, whereas 209 lesions were described on HRCT. The frequencies of lesions in the lung regions were similar between LUS and HRCT. In both examinations, lesions in the lower parts of the lungs were most often reported (LUS 60.9% vs. HRCT 55.5%) and least often in the upper parts of the lungs (LUS 12.7% vs. HRCT 12.0%). The most frequently described lesions were LUS consolidations (99; 22.8%) and HRCT fibrosis (74; 16.5%). A statistically significant relationship was found in the detection of fibrosis in 11 of the 12 regions (phi = 0.40–1.0). Maximum values of the phi coefficient for the upper part of the left lung were recorded. Compared with HRCT, LUS is an effective alternative for evaluating and monitoring pulmonary lesions in adult patients with PADs, especially for pulmonary fibrosis.